Genetic medicine: an experiment in community-expert interaction - Schibeci, R. (Journal of medical ethics, 1999)
This project tested a two-way model of communication between lay groups and experts about genetic medicine in Perth, Western Australia. Focus group discussion with community group participants was followed by a communication workshop between community group participants and experts. Four groups of concerns or themes emerged from discussion: clinical considerations; legislative concerns; research priorities, and ethical and wider considerations. Community group concerns are not always met by the actions of "experts". This is, in part, because of the differing life-worlds of each group. However, the communication workshop showed the potential of two-way communication for both lay and expert members in understanding the others' viewpoint. Further, the approach developed here offers one possible way for community groups to participate in a substantial way in policy formulation processes.